Activation of inflammatory immune gene cascades by lipopolysaccharide (LPS) in the porcine colonic tissue ex-vivo model. (2nd August 2016) - Bahar, B; O'Doherty, J V; Vigors, S; Sweeney, T
Summary: The technique of challenging postmortem tissue explants with inflammation inducer such as lipopolysaccharide (LPS) followed by gene expression analysis is used widely for evaluating the immune-suppressing effect of bioactives. Using porcine colonic tissue as an ex-vivo model of mammalian intestinal gut, this study evaluated the effect of incubation time on the integrity of gene transcripts and activation of inflammatory immune gene cascade by LPS treatment. Post-slaughter colon was removed surgically and explants were incubated for 0, 3, 6 and 12 h and the abundance of mRNA transcripts of a panel of 92 immune genes were evaluated using quantitative polymerase chain reaction (qPCR) arrays. The mRNA transcripts were highly intact after 0 and 3 h of incubation; however, after 6 h the degradation was clearly evident. Following 3 h incubation, 98·8% and 100% mRNA transcripts were detectable in the colonic tissue harvested from weaned and mature pigs, respectively. In the explants of weaned piglets, LPS treatment activated inflammatory signalling pathways [high mobility group B1 (HMGB1), dendritic cell maturation, interleukin (IL)-6, IL-8, IL-17F], while these pathways were inhibited by dexamethasone treatment. Activations of inflammatory genes were also evident in the explants collected from the mature pigs subjected to ex-vivo incubation for 3 h in the absence or presence of LPS. It is concluded that the colonic explant remains physiologically viable and responsive to immunological challenge for up to 3 h ex-vivo . Graphical Abstract: